MOTIF PENGGUNA DALAM MEMANFAATKAN AKUN TWITTER KELAS SEBAGAI MEDIA KOMUNIKASI ONLINE - Dewi, Nilam Chandara; Hastasari, Chatia; Wisudawanto, Rahmat (KOMUNITAS, 2014)
Nowdays, one of  the well-known  means of communication is internet or also known as the new media. The internets is used as a main source for communicating and searching for information. This very media is what no longer makes distance and time a problem. The internet has developed and become an efficient  and  effective  way  of  communication.  The  internet  has  grown  into  a  communicative  mean  and cannot  be  disregarded.  Internet  users  are  mostly  students,  due  to  the  facilities  being  easy  to  use  and accessed. Most people use internet connection to receive information and entertainment. Accordingly to the Mcquail application which states that there are four  motives on the usage of media,  1.  Information  (surveillance)  with  four  subs:  a.  seeking  news  regarding  events  and  conditions relevant  with  the  closest  environment,  society,  and the  world.b.Seeking  for  guidance  on  practical issues,  opinions  and  such  which  are  related with  choosing  an  option,  c.To  fulfill  curiosity  and public interest,  d.  To learn, self- education,  2. Personal identit motives consists of four subs:  a.  To find support on personal  values,b.To  find  a behavior  model,  c.To  identify  oneself  with  other  values  found within  the media,  d.To  gain  an  understanding  of  oneself.  3.  Integration  and  social  interaction  motives  (Personal Relationship) consists of six sub chapters:  a.  To obtain knowledge regarding the circumstances of  others, b.  To identify oneself with  others  and gain  a  sense  of belonging,  c.To  find  conversation  material  and social  interaction,  d.  To gain friends  beside  humans,  e.  To  assist social  role,  f.  Makes connecting with family, friends and society possible.  4. For entertainment motives (Diversion) there are five sub chapters: a.  To  release  oneself  from  problems,  b.To  relax,  c.To  achieve  spiritual joy  and esthetical joy,  d.  To fill time, e.To channel emotions, f. To stimulate sexual desires. It  may be  concluded that the  aforementioned  theories  stated by McQuail  are proven  by twitter accounts of class XI class of 2013 students of SMA  Negeri Surakarta within the period of November until December, aside from that the writer has also foundchanging motives which happens within information motives and entertainment motives.